MENGKAJI PEMAHAMAN UMAT TENTANG LITURGI SABDA DALAM PERAYAAN EKARISTI DI PAROKI SANTO YOSEPH NAIKOTEN KEUSKUPAN AGUNG KUPANG - Rusae, Yohanes (Pastoralia Jurnal Penelitian Dosen, 2023)
The celebration of the Eucharist is central to all Catholic life. There are four parts to the celebration of the Eucharist: the Opening Rites, the Liturgy of the Word, the Liturgy of the Eucharist, and the Closing Rites. In the Liturgy of the Word there are readings of Scripture, psalms, homilies and prayers of the people. People believe that Christ Himself speaks through His Word. In this research the author uses a qualitative research method using content analysis in which problems or findings in the field are verified with empirical data. Researchers use a descriptive level of explanation, so that they hear more input from informants as a data source in order to find the root of the problem. The results of this research show that the people do not properly appreciate the celebration of the liturgy of the Word because the main inhibiting factor is the absence of catechesis or socialization about the Liturgy of the Word and also the lack of awareness within the people about the Liturgy of the Word in the Eucharist Celebration. So, from the results of this research, it is hoped that the parish can provide outreach regarding the liturgy of the Word for the people.